Biogenically fabricated Tulsi-infused ZnO–CuO nanocomposites for enhanced dye reduction and adsorption - Hisana; Adnan Shahzaib; Nahid Nishat; Saad M. Alshehri; Tansir Ahamad; Zeba Haque (Hybrid Advances, 2024)
This study explores the green synthesis of ZnO–CuO nanocomposites (NCs) using Tulsi (Ocimum sanctum) leaf extract as a reducing and stabilizing agent. Structural characterization confirms the crystalline nature and the hexagonal wurtzite and monoclinic phases of ZnO and CuO, respectively. Scanning electron microscopy reveals aggregated nanoparticles with an average size of 109 nm. Energy-dispersive X-ray spectroscopy confirms the presence of Zn, Cu, and O in the NCs. Notably, the NCs exhibit a narrow band gap of 2.4 eV. These nanocomposites demonstrate remarkable catalytic efficiency in reducing toxic Congo red and methyl orange dyes, with high rate constants of 0.43 and 1.01 min−1, respectively. Optimal Congo red adsorption occurs at 25 % dye concentration and 70 min contact time. The adsorption kinetics follow the pseudo-second-order model, indicating chemisorption. The Freundlich isotherm accurately describes the multilayer, heterogeneous adsorption phenomenon. This green synthesis method successfully produces ZnO–CuO nanocomposites with significant potential for organic pollutant treatment and environmental remediation applications.